Designing a Web-Based Enterprise Resource Planning System Using the CodeIgniter Framework for Business Process Optimization - Joko Riyanto; Windy Naila Sarifah; Arinkha Damayanti (Jurnal Teknoinfo, 2026)
Enterprise Enterprise Resource Planning (ERP) is an integrated system designed to improve efficiency and accuracy in company information management. This study aims to design and implement a web-based ERP system at CV Triraksa Jaya Mandiri as a solution to various operational issues, such as manual data processing, reporting delays, and a lack of integration between divisions. The system development method applied is Extreme Programming (XP), as it is flexible to changes and supports rapid iterations. The system consists of seven main modules: Finance, Human Resources, Supply Chain Management, Customer Relationship Management, Warehouse Management System, Document Management, and Business Intelligence. The technologies used include the CodeIgniter 4 framework, Bootstrap 5, Chart.js, PhpSpreadsheet, DomPDF, and MySQL as the database. The implementation results show that the system streamlines business processes, improves operational efficiency, and produces accurate real-time reports. The Business Intelligence module is capable of presenting financial and operational data in the form of graphical visualizations and insights based on actual data trends. The system has been tested using User Acceptance Testing and has demonstrated a high level of user satisfaction. This study proves that a web-based ERP is an effective solution to support the digitalization of business processes in small and medium enterprises (SMEs).